Rural Electrification : Lessons Learned - Sanghvi, Arun; Barnes, Douglas (2012)
The note focuses on the external benefits of rural electrification (RE), i.e., improved access to communication, education, and economic opportunities, in addition to extended health services. It outlines key lessons to scaling up RE, namely macroeconomic stability, continued government commitments, and institutional capacity. However, it also suggests that grid extension is not always cost-effective, rather, decentralized delivery options, and alternative energy sources, such as solar photovoltaic, mini-hydro, and other renewable energy sources should be considered. Moreover, good practices indicate the need for power sector reform, regulatory framework with legal guarantees that utilities can operate autonomously, and, financial viability, that is, to ensure commercialization, and identify a cost-recovery system that takes into account capital investment costs, and contributions levels. Strongly emphasized is the involvement of local communities in the design, and implementation of RE, by setting rural electrification committees, and by establishing institutional, and organizational procedures for project planning.